The typology of vocational education and training cooperation between Germany and China - Shan Zhu; Wolfgang Meyer; Selina Röhrig (International Journal of Training and Development, 2022)
Germany and China have been engaged in a wide range of vocational education and training (VET) cooperation activities since the 1980s. To clarify what organizations have been involved and what project types exist within VET cooperation, a semistructured survey had been conducted for collecting data. By this approach, 99 VET project profiles with 258 organizations related were detected. To analyse these projects and organizations, the `general key factor model of sustainability'~is used to structure the analysis framework. In this framework, `cooperation type', `content type'~and `project duration'~were considered as the three fundamental criteria for further categorization. On this basis, seven cooperation types were created by the organizations involved, three content types were established by the goal of the project~and three project duration were distinguished by the time planned for the project. The result shows that governmental organizations are the main actors who play a major role in the Sino-German VET cooperation. However, numerically, German private organizations participated more in VET cooperation rather than Chinese private organizations. Civil social organizations show no significant function. Meanwhile, different cooperation types show different projects' emphasis: Type G (Governmental) projects focus on building or promoting on the organization level; Type G0.167em+0.167emP (Governmental0.167em+0.167emPrivate) projects tend to objectives on the individual and system level; Type G0.167em+0.167emC (Governmental0.167em+0.167emCivil) projects occur more often at an individual level;~Type G0.167em+0.167emP0.167em+0.167emC (Governmental0.167em+0.167emPrivate0.167em+0.167emCivil) projects tend to pursue goals on organizational or system level.
Keywords: 650